PROBLEMS OF TEACHING EXACT SCIENCES IN VOCATIONAL SCHOOLS - Saydaliyeva Umidaxon Momirovna (Лучшие интеллектуальные исследования, 2024)
Abstract: This article focuses on the current issues of teaching specific sciences in professional educational institutions. Attention is also paid to the content of reforms and legal documents implemented in the field.